Effect of Zn-Rich Wheat Bran With Different Particle Sizes on the Quality of Steamed Bread - Wang, Huinan; Li, Anfei; Kong, Lingrang; Zhang, Xiaocun (Frontiers in Nutrition, 2021)
Bran is the main by-product of wheat milling and the part of the grain with the highest Zn content. We investigated the effects of the particle sizes (coarse, D50 = 375.4 ± 12.3 μm; medium, D50 = 122.3 ± 7.1 μm; and fine, D50 = 60.5 ± 4.2 μm) and addition level (5%–20%) of Zn-biofortified bran on the quality of flour and Chinese steamed bread. It was studied to determine if the Zn content of steamed bread could be enhanced without deleterious effects on quality. Dough pasting properties, such as peak viscosity, trough viscosity, final viscosity, breakdown, and setback, decreased significantly as the bran addition level was increased from 5% to 20% but did not significantly differ as a result of different bran particle sizes. Bran incorporation significantly increased hardness, gumminess, chewiness, and adhesiveness, whereas the springiness, cohesiveness, and specific volume of steamed bread decreased with the increase in bran addition. The optimal sensory score of steamed bread samples in the control and Zn fertilizer groups were obtained under 5% bran addition resulting in comparable flavor, and texture relative to control. Meanwhile, the Zn content of the steamed bread in the Zn fertilizer group was 40.2 mg/kg, which was 55.8% higher than that in the control group. Results indicated that adding the appropriate particle size and amount of bran would be an effective and practical way to solve the problem of the insufficient Zn content of steamed bread.